2014
DOI: 10.1155/2014/913696
|View full text |Cite
|
Sign up to set email alerts
|

Helminth Parasites Alter Protection againstPlasmodiumInfection

Abstract: More than one-third of the world's population is infected with one or more helminthic parasites. Helminth infections are prevalent throughout tropical and subtropical regions where malaria pathogens are transmitted. Malaria is the most widespread and deadliest parasitic disease. The severity of the disease is strongly related to parasite density and the host's immune responses. Furthermore, coinfections between both parasites occur frequently. However, little is known regarding how concomitant infection with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 161 publications
0
34
1
Order By: Relevance
“…It has been suggested that, during chronic helminthiases, this anti-inflammatory network may play a key role in the lower prevalence of allergic disease observed in Th2-skewed populations [7, 1012]. Conversely, helminth-induced IL-10-mediated immunosuppression has raised concerns for populations in which STH infections coexist with other morbidities such as HIV/AIDS, malaria, and tuberculosis, as clearance for the latter depends on an active and timely type-1 response [8, 1316]. …”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that, during chronic helminthiases, this anti-inflammatory network may play a key role in the lower prevalence of allergic disease observed in Th2-skewed populations [7, 1012]. Conversely, helminth-induced IL-10-mediated immunosuppression has raised concerns for populations in which STH infections coexist with other morbidities such as HIV/AIDS, malaria, and tuberculosis, as clearance for the latter depends on an active and timely type-1 response [8, 1316]. …”
Section: Introductionmentioning
confidence: 99%
“…Malaria and helminth infection are the most important public-health problems affecting children in Sub-Saharan Africa [ 1 ]. It is estimated that over a third of the world's population, mainly those individuals living in the tropics and subtropics, are infected by parasitic intestinal helminths or one or more of the species of Plasmodium [ 2 ]. Malaria caused by Plasmodium falciparum is responsible for a high burden of disease and a loss of growth in endemic countries estimated to be as high as 1.3% of gross domestic product per year [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acute infection of STH will increase the Th1 system that can be protective against malaria infection. Meanwhile, the chronic infection of STH will suppress the Th1 system, thus increasing the chances of malaria infection [14].…”
Section: Resultsmentioning
confidence: 99%